2014
DOI: 10.1002/anie.201308984
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Comparison of Peptidic Proteasome Inhibitors Highlights the α‐Ketoamide Electrophile as an Auspicious Reversible Lead Motif

Abstract: The ubiquitin-proteasome system (UPS) has been successfully targeted by both academia and the pharmaceutical industry for oncological and immunological applications. Typical proteasome inhibitors are based on a peptidic backbone endowed with an electrophilic C-terminus by which they react with the active proteolytic sites. Although the peptide moiety has attracted much attention in terms of subunit selectivity, the target specificity and biological stability of the compounds are largely determined by the react… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
91
0
9

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 82 publications
(107 citation statements)
references
References 32 publications
4
91
0
9
Order By: Relevance
“…11 Recently, it was shown that the α-ketoamide motif is a peptide C-terminus electrophilic motif, leading to reversible inhibitors conversely to most of covalent inhibitors. 12 Neglected during a long period, noncovalent inhibitors introduce today a plausible alternative mechanism of inhibition to that of covalent inhibitors. 8,13 Inhibitor noncovalency favors deep solid tissue penetration, and noncovalent inhibitors can be more specific, stable, and less reactive than the covalent ones.…”
Section: ■ Introductionmentioning
confidence: 99%
“…11 Recently, it was shown that the α-ketoamide motif is a peptide C-terminus electrophilic motif, leading to reversible inhibitors conversely to most of covalent inhibitors. 12 Neglected during a long period, noncovalent inhibitors introduce today a plausible alternative mechanism of inhibition to that of covalent inhibitors. 8,13 Inhibitor noncovalency favors deep solid tissue penetration, and noncovalent inhibitors can be more specific, stable, and less reactive than the covalent ones.…”
Section: ■ Introductionmentioning
confidence: 99%
“…[8] They first determined the substrate preference of the parasite proteasome by analyzing the degradation pattern of 228 divergent peptides. [9] Upon comparison with the EM structure of the human constitutive proteasome, [10a] it became clear that the b2b inding pocket is broader and more open in the parasite than in humans,t hus enabling an easier fit of the tryptophan at the P3 position. Since at ryptophan residue at these positions is favored in protozoa, three peptide-based vinyl sulfones (WLW-vs,WLL-vs,and LLW-vs) were employed and their activities evaluated in vitro with purified P. falciparum CP.R emarkably,t he three compounds predominantly displayed activity towards the parasite b2s ubunit, whereas the human b2site was hardly affected.…”
mentioning
confidence: 99%
“…[11] Recently, extensive research on the optimization of peptide backbones by incorporation of unnatural amino acids resulted in b5i-and b5c-specific epoxyketones. [14][15][16] Notably, PSF compounds block the CP activity in the low nanomolar range, [16] albeit they are the only peptidic CP inhibitors known so far whose electrophilic headgroup is shifted by a methylene unit, which demands an exceptional binding mode. [14][15][16] Notably, PSF compounds block the CP activity in the low nanomolar range, [16] albeit they are the only peptidic CP inhibitors known so far whose electrophilic headgroup is shifted by a methylene unit, which demands an exceptional binding mode.…”
mentioning
confidence: 99%